Successful Mechanical Thrombectomy of a Middle Cerebral Artery Occlusion 14 Hours after Stroke Onset - Anelia Dietmann; Kety Wha-Vei Hsieh; Andrea M. Humm; Claudio L. Bassetti; Urs Fischer; Jan Gralla (Case Reports in Neurological Medicine)
A 54-year-old patient presented with mild right-sided weakness of hand and face with a National Institutes of Health Stroke Scale (NIHSS) of 2 and occlusion of the left middle cerebral artery (MCA) in the M1 segment with a large perfusion deficit on computed tomography (CT). Due to mild neurological deficits no IVT was performed. Nine hours after symptom onset the patient gradually deteriorated with a NIHSS fluctuating between 9 and 15. MRI showed a persistent occlusion of the MCA with a large diffusion-perfusion mismatch. Immediate endovascular thrombectomy was performed 14 hours after symptom onset with complete recanalization and complete clinical recovery. Although mechanical thrombectomy is generally considered an effective alternative strategy up to 8 hours after stroke onset, selected patients with a large diffusion/perfusion mismatch and small infarct cores may benefit from an expanded therapeutic window.